2019
DOI: 10.12932/ap-070219-0488
|View full text |Cite
|
Sign up to set email alerts
|

The association of plasma cytokines including VEGF with recurrent wheezing in allergic patients

Abstract: Background: Various cytokines have been studied to determine their functions in the pathogenesis of allergic diseases and their potential as therapeutic targets, but the roles and clinical applicability of many of these cytokines still remain unclear.Objective: We aimed to measure the plasma levels of eight cytokines known to be relevant to allergic diseases, and to determine their association with the diagnostic characteristics of allergic patients. Methods:The levels of a panel of eight cytokines (IL-5, IL-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
(39 reference statements)
1
1
0
Order By: Relevance
“…Most of them reported a stronger severity of asthma symptoms or higher exacerbations in obese patients, characterized by increased leptin levels and low adiponectin levels, compared with their non-obese counterparts. These results are supported by other studies [48,49], including the French EGEA study, which found that patients with severe asthma were characterized by high leptin levels, poor lung function, a chronic cough, high BMI, and high circulating neutrophil levels [50]. In addition, weight loss was associated with significant changes in the systemic and pulmonary inflammatory profiles in asthmatic patients, leading to a better control due to an increase in some anti-inflammatory mediators (e.g., adiponectin) and a reduction in pro-inflammatory mediators, including leptin [51].…”
Section: Discussionsupporting
confidence: 91%
“…Most of them reported a stronger severity of asthma symptoms or higher exacerbations in obese patients, characterized by increased leptin levels and low adiponectin levels, compared with their non-obese counterparts. These results are supported by other studies [48,49], including the French EGEA study, which found that patients with severe asthma were characterized by high leptin levels, poor lung function, a chronic cough, high BMI, and high circulating neutrophil levels [50]. In addition, weight loss was associated with significant changes in the systemic and pulmonary inflammatory profiles in asthmatic patients, leading to a better control due to an increase in some anti-inflammatory mediators (e.g., adiponectin) and a reduction in pro-inflammatory mediators, including leptin [51].…”
Section: Discussionsupporting
confidence: 91%
“…The pathogenic effects of leptin and M1 macrophages can be verified in asthmatic patients. Obese asthmatic patients with higher serum leptin levels and BMI are more likely to have severe clinical symptoms than nonobese asthmatic patients (Nadif et al 2020 ; Chang et al 2022 ; Zhang et al 2017 ). Patients with obesity-related asthma are mostly characterized by low serum IgE levels and low numbers of eosinophils in sputum (Telenga et al 2012 ; Gibeon et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%